Development and Evaluation of Pulp and Paper Properties Using Bambusa Vulgaris - KADAR MYDIN, NURFIRZANA; MAIN, NOR MAZLANA (Progress in Engineering Application and Technology, 2023)
The research aimed to determine the potential value for pulp and paper making using 18% and 22% of active alkali (AA) charge on Bambusa Vulgaris (Buluh Minyak). Soda pulping was used for pulping process. The condition of pulping that were use are 18% and 22% AA, with 2 hours cooking time. The pulp, paper production and properties were conducted according to the TAPPI and MS ISO standard. A basis weight of 80 g/m² was used for paper sheet formation.  Pulp from 18% AA resulted in 31% of screened yield whereas 22% AA resulted in 38.95%. 18% AA provided the strongest tear and tensile strength index with the value of 8.52 mNm²/g and 2.53 Nm/g, respectively. However, the 18% AA showed lower burst index with the value of 3.71 kPa.m2/g. Meanwhile, 22% AA resulted in tear strength of 8.374 mNm²/g, tensile strength index of 1.48 Nm/g however higher in burst index with the value of 4.36 kPa.m²/g. Based on ANOVA analysis, there is a significant difference for tensile and bursting strength except for tearing strength since there is no significant different between both pulping conditions. Based on overall result, it was clear that 22% of AA contributes to best pulp production. Nevertheless, 18% of AA contributes to the best paper properties due to the higher value of tensile and tear strength. Buluh Minyak fiber with the soda pulping characterization has high potential to be used in the production of paper making industry. The findings of this study will also serve as a disclosure to establish and innovate sustainable paper production while preventing environmental contamination.